2018
DOI: 10.1111/ejn.14057
|View full text |Cite
|
Sign up to set email alerts
|

Singing activity‐driven Arc expression associated with vocal acoustic plasticity in juvenile songbird

Abstract: Learned vocalization, including birdsong and human speech, is acquired through self‐motivated vocal practice during the sensitive period of vocal learning. The zebra finch (Taeniopygia guttata) develops a song characterized by vocal variability and crystallizes a defined song pattern as adulthood. However, it remains unknown how vocal variability is regulated with diurnal singing during the sensorimotor learning period. Here, we investigated the expression of activity‐dependent neuroplasticity‐related gene Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…We administrated T to juvenile zebra finches before the onset of first singing at 30 phd. We observed a decrease in acoustic variability across song bouts in T‐implanted juvenile zebra finches 2 weeks after of T‐implantation (Hayase & Wada, ). At this developmental time point (47.64 ± 2.9 phd), we compared their chrm2 expression level in HVC with that of age‐matched normal juveniles.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We administrated T to juvenile zebra finches before the onset of first singing at 30 phd. We observed a decrease in acoustic variability across song bouts in T‐implanted juvenile zebra finches 2 weeks after of T‐implantation (Hayase & Wada, ). At this developmental time point (47.64 ± 2.9 phd), we compared their chrm2 expression level in HVC with that of age‐matched normal juveniles.…”
Section: Resultsmentioning
confidence: 90%
“…Exogenous testosterone (T) was implanted as described before (Hayase & Wada, ). Each bird was anesthetized by an intraperitoneal injection of pentobarbital (6.48 mg/ml; 60 μl/10 g body weight).…”
Section: Methodsmentioning
confidence: 99%
“…Singing behavior generates robust neuronal activity in the song system, including RA and other song nuclei, throughout a bird’s life from juvenile to adult stages [ 31 , 48 , 59 61 ]. However, some immediate-early genes are more highly induced by singing in the song nuclei (e.g., egr1 [ zenk ] and Arc in RA and penk in HVC) in juvenile than adult stages, although the causal reason of the developmental different induction is not known [ 13 , 17 19 ]. In this study, we found that RA shows a reduction of singing activity–dependent gene induction during the accumulation of singing experience.…”
Section: Discussionmentioning
confidence: 99%
“…Developed slides were Nissl-stained with a cresyl violet acetate solution (Sigma) for the capture of high-resolution images. For quantification of mRNA signal, exposed X-ray films of brain images were digitally scanned under a microscope (Leica, Z16 APO) connected to a CCD camera (Leica, DFC490) with Application Suite V3 imaging software (Leica), as previously described [ 12 , 13 , 19 , 20 ]. To minimize handling bias for signal detection among experimental groups, we performed in situ hybridization using multiple brain sections at once for each probe and exposed S 35 -riboprobe hybridized brain sections on the same sheet of X-ray films.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation